2015
DOI: 10.1111/wre.12144
|View full text |Cite
|
Sign up to set email alerts
|

Under‐sown cover crops and post‐harvest mowing as measures to control Elymus repens

Abstract: Two potential control methods for Elymus repens, which do not disturb the soil, are post-harvest mowing and competition from under-sown cover crops. Our aim was to quantify the effect of cover crop competition and mowing on E. repens and to evaluate the potential for combining the two methods. We present a two-factorial split-plot experiment conducted at three locations in Sweden, in two experimental rounds conducted in 2011-2012 and 2012-2013. A spring cereal crop was under-sown with perennial ryegrass, red c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 16 publications
(24 reference statements)
3
45
0
2
Order By: Relevance
“…Short-term mowing studies for other perennial species have also generally shown a lack of or inconsistency in efficacy (Bicksler and Masiunas 2009;Schooler et al 2010;Summerlin et al 2000;Stanley et al 2011). Several years and greater withinseason frequencies of mowing may be necessary to see any effect on long-lived perennial species, especially in terms of depletion of root reserves (Hakansson 1969;Ringselle et al 2015).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Short-term mowing studies for other perennial species have also generally shown a lack of or inconsistency in efficacy (Bicksler and Masiunas 2009;Schooler et al 2010;Summerlin et al 2000;Stanley et al 2011). Several years and greater withinseason frequencies of mowing may be necessary to see any effect on long-lived perennial species, especially in terms of depletion of root reserves (Hakansson 1969;Ringselle et al 2015).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Shoot density grading was performed four times in Y1 (2 weeks after emergence of the main crop, before harvest, 20 days after harvest, and in November before ploughing) and three times in Y2 (2 weeks after emergence of the main crop, before harvest and 20 days after harvest). This was done using a 'grading fork' consisting of a frame 36 cm long with four 28 cm long tines, creating three inter-tine areas of 333 cm 2 each (Ringselle et al 2015). Occurrence/nonoccurrence of at least one shoot in each inter-tine area was recorded, giving a value between 0 and 3.…”
Section: Methodsmentioning
confidence: 99%
“…Couch grass control Ringselle et al (2015) concluded that repeated mowing during autumn can reduce couch grass rhizome biomass, but a low-yielding cover crop (30-60 g m -2 in October) will only reduce autumn shoot biomass, and not the rhizome biomass. The rhizome biomass can be viewed as accumulated biomass reflecting the growing conditions during the whole season and perhaps previous seasons, while the shoot biomass adjusts faster to the prevailing conditions.…”
Section: Phosphorus Leachingmentioning
confidence: 99%
See 1 more Smart Citation
“…This often leads to increasing problems with perennial weeds. Undersown cover crops and post-harvest mowing after the main crop harvest may help to control perennial weeds (Aronsson et al 2015, Ringselle et al 2015a), but cover crops have not always been effective (Brandsaeter et al 2012). …”
Section: Introductionmentioning
confidence: 99%